The Central Role of Salivary Metalloproteases in Host Acquired Resistance to Tick Feeding - Perner, Jan; Helm, Dominic; Haberkant, Per; Hatalova, Tereza; Kropackova, Sara; Ribeiro, Jose M.; Kopacek, Petr (Frontiers in Cellular and Infection Microbiology, 2020)
During feeding on vertebrate hosts, ticks secrete saliva composed of a rich cocktail of bioactive molecules modulating host immune responses. Although most of the proteinaceous fraction of tick saliva is of little immunogenicity, repeated feeding of ticks on mammalian hosts may lead to impairment of tick feeding, preventing full engorgement. Here, we challenged rabbits with repeated feeding of both Ixodes ricinus nymphs and adults and observed the formation of specific antibodies against several tick salivary proteins. Repeated feeding of both I. ricinus stages led to a gradual decrease in engorged weights. To identify the salivary antigens, isolated immunoglobulins from repeatedly infested rabbits were utilized for a protein pull-down from the saliva of pilocarpine-treated ticks. Eluted antigens were first identified by peptide mass fingerprinting with the aid of available I. ricinus salivary gland transcriptomes originating from early phases of tick feeding. To increase the authenticity of immunogens identified, we also performed, for the first time, de novo assembly of the sialome from I. ricinus females fed for six days, a timepoint used for pilocarpine-salivation. The most dominant I. ricinus salivary immunogens identified in our study were zinc-dependent metalloproteases of three different families. To corroborate the role of metalloproteases at the tick/host interface, we fed ticks micro-injected with a zinc metalloprotease inhibitor, phosphoramidon, on a rabbit. These ticks clearly failed to initiate feeding and to engorge. However, neither feeding to ticks immune blood of repeatedly infested rabbits, nor phosphoramidon injection into ticks, prevented their engorgement when fed in vitro on an artificial membrane system. These data show that Zn metalloproteases play a decisive role in the success of tick feeding, mediated by complex molecular interactions between the host immune, inflammatory, and hemostatic processes, which are absent in in vitro feeding. This basic concept warrants further investigation and reconsideration of the current strategies towards the development of an effective “anti-tick” vaccine.